Controlling the Charge Density Wave Transition in Monolayer TiSe2: Substrate and Doping Effects. Issue 3 (11th October 2018) - Kolekar, Sadhu; Bonilla, Manuel; Diaz, Horacio Coy; Hashimoto, Makato; Lu, Donghui; Batzill, Matthias
Abstract: TiSe2 is an exciting material because it can be tuned between superconducting and charge density wave (CDW) transitions. In the monolayer limit, TiSe2 exhibits a sizable energy gap in the CDW phase that makes it a promising quantum material. It is shown that interfacing a single layer of TiSe2 with dissimilar van der Waals materials enables control of its properties. Using angle‐resolved photoemission spectroscopy, the energy gap opening is analyzed as a function of temperature for TiSe2 monolayers supported on different van der Waals substrates. A substantial increase in the CDW transition temperature of ≈45 K is observed on MoS2 compared to graphite (highly oriented pyrolytic graphite) substrates. This control of the CDW in monolayer TiSe2 is suggested to arise from varying charge screening of the unconventional CDW of TiSe2 by the substrate. In addition, the suppression of CDW order and a complete closing of the energy gap by electron doping of monolayer TiSe2 is demonstrated. Regulating the many‐body physics phenomena in monolayer TiSe2 lays the foundation of modifying TiSe2 in, for example, artificial van der Waals heterostructures and thus creates a new approach for utilizing the quantum states of TiSe2 in device applications. Abstract : TiSe2 is balanced between unconventional charge order state and superconductivity . Herein, it is demonstrated that for single layers, the charge order transition can be tuned by over 50 K by interfacing with different substrates. Moreover, the transition can be completely suppressed by electron doping. This control of the quantum states makes monolayer TiSe2 an especially exciting material.